A comparative study of embryonic gene expression in Drosophila and Ephestia. - Leibenguth, F.; Rammo, E.; Dubitsky, R. (Wilhelm Roux's archives of developmental biology, 1979)
The ontogeny of allozyme patterns has been studied in embryos ofDrosophilamelanogaster, which are doubly heterozygous for alleles specifying the slow and fast forms of alcohol dehydrogenase (ADH) and ?-glycerophosphate dehydrogenase (GPDH). The ontogeny of esterase-2 was studied in embryos and young larvae of the flour mothEphestia kühniella, which are heterozygous for two of the three existing esterase-2 alleles. In freshly laidDrosophila eggs only the maternal enzyme forms are present and during the first 15 hours of development the staining of these forms becomes progressively fainter. After 16 and 17 h, the paternal and hybrid bands of ADH and GPDH respectively become obvious. Before hatching, the intensity distribution in the three-banded pattern of reciprocal hybrids is asymmetric in favour of the persisting maternal enzyme form. InEphestia embryos, however, there is no persistence of the maternal esterases. In all reciprocal heterozygotes a three-banded pattern suddenly appears 96 h after egg deposition, indicating synchronous activation of both parental alleles. The relative intensity distribution in the hybrid patterns approaches that of the mature larvae stepwise and in an allele-specific manner. This result and the fact that the various heterozygous types exhibit unequal total activities suggest that the Esterase-2 alleles have different activities, which are fixed late in embryogenesis.